Pengaruh Fasilitas Perpustakaan, Kualitas Layanan dan Kinerja Pustakawan Terhadap Minat berkunjung Mahasiswa Universitas Lancang Kuning - Diani Hartati; Bunyamin Ritonga; Deliza Zakir (Jurnal Gema Pustakawan, 2024)
ABSTRACT This research aims to determine the influence of library facilities, service quality and librarian performance on students' interest in visiting the Lancang Kuning University library. This research is a type of quantitative research using a causal research design to measure relationships between variables, or to analyze how one variable influences other variables (Umar, 2002:39). With data collection techniques using questionnaires with a Likert scale, observation and documentation. The sampling technique used was random sampling of 100 respondents obtained using the Slovin formula. The data analysis methods used are statistical analysis, classical assumption test, multiple linear regression, partial t test, simultaneous f test and coefficient of determination testing. Simultaneously, the three variables above, namely library facilities, service quality and librarian performance, have an influence together. This is proven by the results of the regression test which shows that of the three variables library facilities, service quality and librarian performance from the results of the F Statistical Test obtained a Sig value. 0.000 (<5%) in the sense that it is less than the standardized α (0.005), which means that together or simultaneously the variables Library Facilities (X1), Service Quality (X2) and Librarian Performance (X3) have a significant effect on the Student Interest in Visiting variable ( Y). Based on the results of the multiple linear regression test, it shows that the variables of library facilities, service quality and librarian performance together have a significant effect on students' interest in visiting Lancing Kuning University, Pekanbaru. Keywords: Facilities, Service Quality, Librarian Performance, Interest in Visiting